Medical Microbiology - Murray, Patrick R.; Rosenthal, Ken S.; Pfaller, Michael A. (Mosby/Elsevier, 2009)
This fully revised new edition provides a balanced, up-to-date and clinically relevant introduction to microbiology. Case studies with questions teach students to think like a doctor and key information is summarised in boxes.